The GEAR Model and Social Policy on Poverty: An Analytical Integrative Literature Review - Wimmy Haliim (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
The article summarises the explanatory potential of the GEAR (Growth, Empowerment, Adaptability, and Rationality) model for explaining and addressing multidimensional poverty in Indonesia. The investigation solves the persistent question of why poverty remains a systemic problem despite decades of intervention. GEAR is introduced as a mode of analysis that bridges theoretical principles with the empirical problems of poverty, rather than a descriptive approach that summarises interventions. The Integrative Literature Review (ILR) approach was used to systematically search Scopus, ProQuest, ScienceDirect, and Springer Nature Link, identifying 112 peer-reviewed publications published between 2020 and 2025. The resulting literature was synthesised and clustered into ten key areas. To establish coherence, complementarities, and tensions, these areas were critically mapped to the four components of the GEAR model. The analysis shows that GEAR has much in common with empirically validated interventions. Accounting for both enabling and constraining dynamics, the study reveals that GEAR not only consists of descriptive synthesis but also functions as a diagnostic model that may be used to explain the successes and failures of policies focused on reducing poverty. The article concludes that the GEAR model has the potential to guide systemic and adaptive change in Indonesia's social policy landscape.